Isolation and characterization of avian leukosis virus subgroup J associated with hemangioma and myelocytoma in layer chickens in China - Wu, Lan; Li, Youjun; Chen, Xueyang; Yang, Yuxin; Fang, Chun; Gu, Yufang; Liu, Jing; Liang, Xiongyan; Yang, Yuying (Frontiers in Veterinary Science, 2022)
A strain of avian leukosis virus (ALV) belonging to a new envelope subgroup J (ALV-J) emerged in 1988 as a new subgroup of ALV and spread rapidly throughout the world. Due to the infection and spread of ALV-J, the global poultry industry experienced a significant loss. Although the disease had been prevented and controlled effectively by culling domestic chickens in the infected zone, a few field cases of ALV-J infection were reported in China in recent years. This study was conducted to characterize the genome and analyze the lesions and histopathology of the ALV-J strain named HB2020, which was isolated from layer chickens in Hubei Province, China. The full-length proviral genome sequence analysis of ALV-J HB2020 revealed that it was a recombinant strain of ev-1 and HPRS-103 in the gag gene in comparison to ALV-J prototype HPRS-103. In the 3′-untranslated region (3'UTR) of the nucleotide sequence, there were found 205-base pairs (bp) deletion, of which 175 were detected in the redundant transmembrane (rTM) region. Besides, the surface glycoprotein gene gp85 had five mutations in a conservative site, whereas the transmembrane protein gene gp37 was relatively conserved. The animal experiments conducted later on this strain have shown that HB2020 can cause various neoplastic lesions in chickens, including enlarged livers with hemangiomas and spleens with white nodules. Additionally, as the exposure time increased, the number of tumor cells that resembled myelocytes in the blood smears of infected chickens gradually increased. These results indicated that HB2020 on recombination with ALV subgroup E (ALV-E) and ALV-J could induce severe hemangiomas and myelocytomas. This inference might provide a molecular basis for further research about the pathogenicity of ALV and emphasize the need for control and prevention of avian leukosis.